Treatment of End‐stage Kidney Failure without Renal Replacement Therapy. Issue 6 (25th August 2016) - Hole, Barnaby; Tonkin‐Crine, Sarah; Caskey, Fergus J.; Roderick, Paul
Abstract: For the majority of patients with end‐stage kidney failure (ESKF) replacement of excretory renal function by dialysis or transplantation (RRT) can extend life and alleviate symptoms. Historically, the availability of RRT has been insufficient and this remains the case for much of the world. However, RRT is now widely available in healthcare systems of higher income countries. Increasing numbers of elderly patients are developing ESKF. RRT in this population is largely by dialysis, comorbidity is high and life expectancy short. Evidence of effectiveness coupled with the burden of treatment among these individuals has raised concerns that health services in high‐income countries may have moved from an era of unmet need into one of potential over‐treatment. Alongside the requirement to make treatment more patient‐centered, this has driven the development of comprehensive conservative care as an alternative approach for older comorbid individuals with ESKF, with the potential for acceptable symptom control and reduced treatment burden. This paper provides a largely UK‐perspective on treating ESKF without RRT. Emphasis is on the need for high‐quality evidence to inform treatment decisions. Complexities of defining, delivering and improving treatment of ESKF without dialysis care are explored. Quantitative and qualitative evidence are summarized and the relationship with palliative and terminal care examined. A framework is suggested for classifying management of ESKF and recommendations made to improve delivery of nondialysis care in the future. For patients with a poor prognosis, such treatment may not result in significantly different survival or quality of life when compared with dialysis. There is a key need to generate the best possible evidence of person‐centered health outcomes associated with the various treatment options for ESKF and to present this to patients in a balanced, personalized way that allows them to make the treatment decision most appropriate for them.